Cation exchanger mixed matrix membrane (MMM) for lead (II) removal from wastewater - Nurul Farhana, Mohamed Basri (2012)
Many toxic heavy metals have been discharged into the environment as industrial wastes everyday.In all over the world,industry is forced by the regulation body to diminish down the heavy metal content to the acceptable level in their wastewaters effluents.In the current research,cation exchanger mixed matrix membrane (MMM) was developed for the lead (Pb) removal from wastewater.A list of commercial cation resin was screened for highest Pb removal.These resins include Dowex M-31,Dowex MAC-3,Amberlite IR-120, Lewatit SP 112,Amberlite IRC-86, Lewatit TP-214,Amberlite IRN-150 and Dowex Marathon MSC.Dowex M-31 cation resin was incorporated into ethylene vinyl alcohol based polymer at different resin loading range from 10 – 30 weight % to prepare cation MMM.In a batch experiment,several parameters were optimized including Pb (II) concentration between 100 to 2000 mg/L,pH between 1 to 8,contact time between 3 to 12 hours and the amount of absorbent from 0.1 to 1 g. Adsorption isotherm for the cation MMM and ground resin were follow to Langmuir isotherm.The increase in resin loading will increase the binding capacity of cation MMM up to a limitation of 50 wt% resin loading.The concept of MMM was successfully expanded to the application of heavy metal removal.